The effects of procrastination on physical activity among Chinese university students: the chain-mediated effects of time management disposition and exercise motivation - Zhang, Yuan; Tian, Maoshen; Yang, Jian; Xi, Yue; Li, Zhihui; Wang, Lin (Frontiers in Psychology, 2024)
Objectives: Grounded in self-determination theory (SDT), the procrastination-health model and the mechanism model of exercise persistence，this study examined the effects of procrastination on physical activity and the mechanism of its action in Chinese college students. Design: Cross-sectional study. Methods: A total of 957 Chinese university students (Mage = 20.26, SD = 1.07) completed questionnaires. The Aitken Procrastination Questionnaire, the Adolescent Time Management Dispositions Scale (ATMDS), the Modified Physical Activity Motivation Measure-Revised (MPAM-R), and the Physical Activity Rating Scale (PARS-3) were used to measure procrastination, time management disposition, exercise motivation, and physical activity. Results: Procrastination, time management disposition, exercise motivation, and physical activity were each significantly correlated, and procrastination was a significant negative predictor of physical activity. The mediating effect of time management disposition and exercise motivation in the effect of procrastination on physical activity was significant, and the mediating effect accounted for 44.65% of the total effect. Three paths were specifically included: first, the separate mediating effect of time management disposition, second, the separate mediating effect of exercise motivation, and third, the chain mediating effect of time management disposition and exercise motivation.This study reveal the internal psychological mechanism of procrastination in Chinese college students' physical activities and provide a theoretical basis for improving time management disposition and exercise motivation by reducing college students' procrastination personality traits and behavioral tendencies, thus better promoting college students' participation in physical activities.